Implementing Classroom Guidance using the Problem-Solving Method to Enhance High School Students’ Learning Responsibility through Group Games - Az-zahroh, Tsania Maulida; Iswantiningtyas, Veny (IKIP Siliwangi, 2025)
This study aimed to determine the effectiveness of implementing the problem-solving method through the “Battle of Brain” group game in enhancing students’ learning responsibility at SMAN 2 Kediri. The research employed a Guidance and Counseling Action Research (GCAR) approach in two cycles. The research sample consisted of second-year students at SMAN 2 Kediri. The instruments used included a learning responsibility questionnaire and an observation guide. The results showed a significant improvement in students’ learning responsibility, with an average increase of 48% in the first and 73% in the second cycles. The findings conclude that classical guidance using the problem-solving method through the “Battle of Brain” simulation game effectively enhances students’ learning responsibility. The implication of this study serves as a foundation for developing classical guidance service programs in schools, particularly using problem-solving approaches and group games to improve students’ sense of learning responsibility.